2013
DOI: 10.20886/jpht.2013.10.3.139-146
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Penguatan Kapasitas Kelompok Tani Hutan Rakyat Di Kabupaten Situbondo

Abstract: Penelitian ini bertujuan untuk mengkaji strategi dalam kegiatan penguatan kapasitas kelompok tani hutan rakyat di Kabupaten Situbondo yang sedang giat mengembangkan hutan di lahan milik. Permasalahan yang dikaji meliputi faktor internal dan eksternal yang mempengaruhi kinerja tani, dan strategi yang efektif dan efisien untuk menguatkan kelompok tani hutan rakyat. Pendekatan analisis yang digunakan adalah analisis matrik evaluasi faktor internal dan ekternal serta strategi interaksi SWOT. Berdasarkan hasil pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…If needed, institutional strengthening is also carried out by increasing the institutional status of LPHD and KUPS. According to Supriono et al [16] several strategies that can be used in strengthening institutional capacity are increasing interest in forest businesses through intensive coaching, utilizing the potential of social capital, the spirit of kinship, mutual cooperation, and self-help of farmers, increasing the role of young farmers who have organizational experience, take advantage of local government support in initiating the formation of cooperatives.…”
Section: Resultsmentioning
confidence: 99%
“…If needed, institutional strengthening is also carried out by increasing the institutional status of LPHD and KUPS. According to Supriono et al [16] several strategies that can be used in strengthening institutional capacity are increasing interest in forest businesses through intensive coaching, utilizing the potential of social capital, the spirit of kinship, mutual cooperation, and self-help of farmers, increasing the role of young farmers who have organizational experience, take advantage of local government support in initiating the formation of cooperatives.…”
Section: Resultsmentioning
confidence: 99%
“…External parties such as local governments, village governments, NGOs, and universities were also consulted about the situation. The involvement of external actors in the capacity building of community institutions is crucial (Galudra 2019;Supriono et al 2013;Wulandari and Inoue 2018). Additionally, building institutional capacity through Article 108 facilitates group business development.…”
Section: Institutional Conditionsmentioning
confidence: 99%
“…External support is linked to aspects of business development, particularly in the formation of farming cooperatives (Supriono et al 2013). However, this study revealed that the number of facilities available for LMDH development was minimal.…”
Section: Rate Of Participation External Support Business Development ...mentioning
confidence: 99%
“…Matriks IFAS dan EFAS digunakan untuk menganalisis faktor-faktor yang menjadi kekuatan, kelemahan (faktor internal) dan peluang, ancaman (Faktor eksternal) (Lewerissa, 2015) dalam pengembangan masoi sebagai HHBK andalan setempat di Kabupaten Teluk Bintuni. Srategi pengembangan masoi dapat ditentukan setelah menganalisis faktor-faktor ekternal dan internal (Supriono et al, 2013). Proses penentuan strategi pengembangan dan penghitungan bobot masingmasing strategi dapat dilihat pada tabel 1 di bawah ini Tabel (Choiria et al, 2012).…”
Section: Teknik Analisis Dataunclassified